Understanding audit quality & talent management of auditors in practice through content analysis & interviews / Ramesh Ruben Louis, Noor Adwa Sulaiman and Zarina Zakaria - Louis, Ramesh Ruben; Sulaiman, Noor Adwa; Zakaria, Zarina (Faculty of Accountancy, 2019)
mainly to accounting scandals arising from questionable accounting practices signed-off by auditors and the inability of auditors to perform audits up to required standards. Researchers and the profession alike have pointed to the talent/human factor as being critical in achieving quality. Objective of the study: To better understand and obtain more information on audit quality and how talent is managed in external audit practices. Method: Content analysis of transparency reports issued by audit practices and interviews with auditors & regulators. Key findings: The content analysis and interviews have provided valuable insights on how the profession defines audit quality and their talent management practices in achieving audit quality. The transparency reports and interviews also provided information on the role audit regulators play in achieving audit quality and its impact on an audit firm’s talent management. The content analysis and interviews were insightful in the areas of talent management policies, ethics management, succession planning and role of regulators as very little prior research has been carried out on these areas in the context of audit quality. Implications: The findings provide a sound foundation of audit quality attributes and talent management practices that are paramount in achieving audit quality as applied by the profession. Together with findings from prior research, these findings can be used to set out a comprehensive talent management framework in the external audit setting for achieving audit quality